’Tommy Atkins’ mango trees subjected to high density planting in subhumid tropical climate in northeastern Brazil - Sousa, Carlos Antônio Ferreira de; Cavalcanti, Maria Irisvalda Leal Gondim; Vasconcelos, Lúcio Flavo Lopes; Sousa, Humberto Umbelino de; Ribeiro, Valdenir Queiroz; Silva, José Algaci Lopes da (Pesquisa Agropecuaria Brasileira, 2012)
The objective of this work was to evaluate the effects of high density planting on 'Tommy Atkins' mango trees cultivated in subhumid warm tropical climate in northeastern Brazil. Treatments consisted of five spacial arrangements of plants (8x5 m, 7x4 m, 6x3 m, 5x2 m and 4x2 m), which resulted in the following plant densities: 250 (control), 357, 555, 1,000 and 1,250 plants per hectare. Plant vegetative and reproductive variables, besides fruit quality parameters, were evaluated at seven and eight years after transplantation to the field. In general, high density planting caused reduction in vegetative and reproductive variables of individual mango trees, but had little influence on fruit quality. Above 555 plants per hectare, a significant decrease was observed in mango tree growth. Furthermore, there were decreases in the percentage of flowering, fruit yield per plant and per area. However, planting density up to 357 plants per hectare, in spite of decreasing plant growth and fruit yield per tree, increases fruit yield per area in 30% in comparison to the control.